Enhancement of the direct power control applied to DFIG-WECS - Hala Alami Aroussi; Elmostafa Ziani; Manale Bouderbala; Badre Bossoufi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This work is dedicated to the study of an improved direct control of powers of the doubly fed induction generator (DFIG) incorporated in a wind energy conversion system 'WECS'. The control method adopts direct power control 'DPC' because of its various advantages like the ease of implementation which allows decoupled regulation for active and reactive powers, as well as a good performance at transient and steady state without PI regulators and rotating coordinate transformations. To do this, the modeling of the turbine and generator is performed. Therefore, the Maximum Power Point Tracking (MPPT) technology is implemented to extract optimal power at variable wind speed conditions. Subsequently, an explanation of the said command is spread out as well as the principle of adjusting the active and reactive power according to the desired speed. Then, the estimation method of these two control variables will be presented as well as the adopted switching table of the hysteresis controller model used based on the model of the multilevel inverters. Finally, the robustness of the developed system will be analyzed with validation in Matlab / Simulink environment to illustrate the performance of this command.